High prevalence of unwanted pregnancies and induced abortions among HIV-infected women from Western India: need to emphasize dual method use?. Issue 1 (2nd January 2016) - Darak, Shrinivas; Hutter, Inge; Kulkarni, Vinay; Kulkarni, Sanjeevani; Janssen, Fanny
Abstract : This study examines the prevalence, reasons, and predictors of unwanted pregnancies and induced abortions among ever married HIV-infected women attending a care facility in Maharashtra, Western India, and discusses its programmatic and policy implications. Retrospectively collected data of pregnancies conceived after the diagnosis of HIV were analyzed using descriptive and logistic regression techniques. Among the 622 women interviewed, 113 women had 158 pregnancies with known outcomes after HIV diagnosis. Among these pregnancies, 80 (51%) were unwanted and 79 (50%) were voluntarily terminated. Fear of transmitting HIV to the child was a frequently mentioned reason for an unwanted pregnancy (71.8%) and induced abortion (59.5%). Women from urban areas [OR 2.43 (95% CI 1.23–4.79)] and with two or more live births before HIV diagnosis [OR 3.33 (95% CI 1.36–8.20)] were significantly more likely to report an unwanted pregnancy. Women with two or more live births before HIV diagnosis [OR 3.16 (95% CI 1.20–8.35)], who did not know that HIV transmission to the baby can be prevented [OR 3.29 (95% CI 1.48–7.34)] and with an unwanted pregnancy [OR 4.82 (95% CI 2.33–10.00)], were significantly more likely to terminate the pregnancy. Despite increased coverage of antiretroviral treatment, effective provision of reproductive healthcare services to HIV-infected women remains challenging. A high prevalence of unwanted pregnancies and induced abortions and a low level of knowledge about prevention of mother to child transmission (PMTCT) underscore the need for preconception counseling and provision of comprehensive family planning services to HIV-infected women. Enrolling all HIV-infected pregnant women, irrespective of their decision to continue with their pregnancy, in the PMTCT program and discussing with HIV-infected women and their partners at HIV diagnosis a full array of contraceptive methods and not just consistent use of condoms might be helpful in reducing unwanted pregnancies.